2008
DOI: 10.1590/s0103-863x2008000200009
|View full text |Cite
|
Sign up to set email alerts
|

Concordância parental sobre problemas de comportamento infantil através do CBCL

Abstract: Resumo: Este estudo versa sobre a concordância entre respostas de pais e mães relativas aos problemas de comportamento do mesmo filho através do instrumento Child Behavior Checklist

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
10

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 20 publications
(14 reference statements)
0
7
1
10
Order By: Relevance
“…52,53 In spite of these differences, the correlations between the PA scale and the RA factor of the PARB-Q on the one hand, and the CBCL scales on the other, were significant, indicating that the instruments assess similar and theoretically related constructs.…”
Section: Discussionmentioning
confidence: 98%
“…52,53 In spite of these differences, the correlations between the PA scale and the RA factor of the PARB-Q on the one hand, and the CBCL scales on the other, were significant, indicating that the instruments assess similar and theoretically related constructs.…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, the possibility of collating the effect of paternal and maternal practices on the children's behavioral problems was reduced. It is important to note that fathers and mothers tend to show little agreement in regard to their children's behavioral problems (Borsa & Nunes, 2008) and also in regard to the way children are raised (Bolsoni-Silva & Loureiro, 2011). One recent study reported that this disagreement was statistically greater in the groups composed of children with externalizing and internalizing difficulties, when compared to groups with children that presented no behavioral problems (Bolsoni-Silva & Loureiro, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…A exemplo disso, um estudo realizado no Brasil (Borsa & Nunes, 2008), objetivou averiguar a concordância entre as respostas das mães e pais aos problemas comportamentais avaliados pelo CBCL, e os resultados apontaram baixa concordância entre as respostas, sinalizando como possível influência os aspectos sociais que delimitam os papéis dos genitores na família e os conflitos na relação intrafamiliar. Ressalta-se que os autores sugerem que em comparação aos pais, as mães tendem a ser mais precisas na avaliação do comportamento dos filhos.…”
Section: Escala De Internalizaçãounclassified